Mangrove Community Structure in West Madapolo Village, North Obi District, South Halmahera Regency - Ode Mantra, Syahrun; Schaduw, Joshian N. W.; Sondak, Calvyn F.A.; Ompi, Medy; Manembu, Indri S.; Wullur, Stenly (Sam Ratulangi University, 2023)
The ecological function of mangroves can be viewed from three aspects, namely physical, chemical, and biological aspects. Data collection of mangrove community structure using line transect quadrant method by pulling the line along 100 m from the sea to land at the lowest tide. The results of mangrove community structure analysis in West Madapolo Village, North Obi District, South Halmahera Regency. Identified 4 types of mangroves namely Rhizopora apiculata, Sonneratia alba, Brugueira gymnorhiza, and Lumnitzera litorea found at the 3 stations. The highest species density value is Rhizopora apiculata, at station 1. The highest frequency by Rhizopora apiculata, and Brugueira gymnorhiza species at station 1 with the same value of 39.29. The highest cover by Rhizopora apiculata species at station 1 with a value of 49.73 and the lowest by S. alba species at 14.17 while the highest importance value index by Rhizopora apiculata species at 147.99 and the lowest is Sonneratia alba 40.54. The highest diversity at station 2, and the lowest at station 1, the highest diversity at station 2 while the highest dominance is found at the station and the lowest at station 2. Keywords: Structure Community, Mangrove, Village Madapolo Barat Abstrak Fungsi ekologis mangrove dapat ditinjau dari tiga aspek, yakni aspek fisika, kimia dan biologi. Pengambilan data struktur komunitas mangrove menggunakan metode line transek kuadran dengan cara menarik line garis sepanjang 100 m dari arah laut ke darat pada saat surut terendah. Hasil analislis struktur komunitas mangrove di Desa Madapolo Barat, Kecamatan Obi Utara, Kabupaten Halmahera Selatan. Teridentifikasi 4 jenis mangrove yaitu Rhizopora apiculata, Sonneratia alba, Brugueira gymnorhiza, dan Lumnitzera litorea yang ditemukan pada ke 3 stasiun. Nilai kerapatan jenis tertinggi adalah Rhizopora apiculata, pada stasiun 1. Frekuensi tertinggi oleh jenis Rhizopora apiculata, dan Brugueira gymnorhiza pada stasiun 1 dengan nilai yang sama yaitu 39,29. Penutupan tertinggi oleh jenis Rhizopora apiculata pada stasiun 1 dengan nilai 49,73 dan yang terendah oleh jenis S. alba 14,17 sedangkan indeks nilai penting tertinggi oleh jenis Rhizopora apiculata 147,99 dan terendah yaitu Sonneratia alba 40,54. Keanekaragaman tertinggi pada stasiun 2, dan terendah pada stasiun 1, kseseragaman tertinggi pada stasiun 2 sedangkan dominasi tertinggi terdapat pada stasiun dan yang terendah pada stasiun 2. Kata kunci: Struktur Komunitas, Mangrove, Desa Madapolo Barat